Magnetic Materials: Rapid, High‐Resolution Magnetic Microscopy of Single Magnetic Microbeads (Small 18/2019). Issue 18 (3rd May 2019) - McCoey, Julia M.; de Gille, Robert W.; Nasr, Babak; Tetienne, Jean‐Philippe; Hall, Liam T.; Simpson, David A.; Hollenberg, Lloyd C. L.
Abstract : In article number1805159, David A. Simpson and co‐workers mount magnetic microbeads (grey: helium ion microscopy) on a diamond with a nitrogen vacancy sensing layer, which reveals the resulting magnetic field (blue‐red). This enables rapid magnetic characterization of bead samples on the individual level, as well as an illumination‐free localization method for biocompatible microbeads.